Optimization and Validation of High Performance Liquid Chromatographic Fingerprint of Phyllanthus niruri - Wulan Tri Wahyuni; Latifah K. Darusman; Aji Hamim Wigena (Universitas Gadjah Mada, 2014)
Split-plot mixture-mixture design has been applied for optimization of Phyllanthus niruri chromatographic fingerprint. The design was applied for unreplicated and simultaneous optimization of extraction mixture and chromatographic mobile phase mixture. The whole-plot was extraction solvent contained various combinations of methanol, ethyl acetate and dichloromethane in a simplex centroid with axial design. The sub-plot was reversed phase chromatographic mobile phase in simplex centroid design contained varying proportions of methanol, acetonitrile and acetonitrile:water (55:45 v/v). Each extract was eluted with seven mobile phases of high performance liquid chromatography and detected at 210, 225 and 254 nm. The optimum condition was determined based on the number of peaks. The correlation between extraction solvent, chromatographic mobile phase and number of peak were evaluated with Ordinary Least Square method. The root mean square error of calibration and root mean square error of prediction obtained at 210, 225 and 254 nm were 1.8634 and 4.0076; 2.2220 and 5.2839; 1.5436 and 2.2606, respectively. The optimum condition was obtained when the ethyl acetate extract was eluted with acetonitrile:water (55:45 v/v) and detected at 254 nm. Precision of retention time at optimum condition was excellent, with the relative standard deviation in a range of 0.0698% and 0.3006%.